Motivasi Pajak, Sanksi Pajak, dan Efektivitas E-Filing pada Kepatuhan Wajib Pajak Orang Pribadi - Dewi, Kadek Anggi Sintya; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 32 No 11 (2022)DO - 10.24843/EJA.2022.v32.i11.p08, 2022)
This study aims to determine the effect of tax motivation, tax sanctions and the effectiveness of e-filing on individual taxpayer compliance at KPP Pratama West Denpasar. The research population is individual taxpayers at KPP Pratama West Denpasar with a total sample of 100 respondents. The data analysis technique in this study is multiple linear regression. The results showed that tax motivation, tax sanctions, and the effectiveness of e-filing had a positive effect on individual taxpayer compliance at the West Denpasar KPP. The implication of this research is that the results of the research conducted provide evidence that individual taxpayer compliance can be influenced by tax motivation, tax sanctions and the effectiveness of e-filing at KPP Pratama West Denpasar. Keywords: Motivation; Sanctions; E-Filing; Taxpayer Compliance